West African food composition table / Table de composition des aliments d’Afrique de l’Ouest - Stadlmayr, B.; Food and Agriculture Organization of the United Nations; International Network of Food Data Systems; West African Health Organization; Bioversity International (2012)
This edition of the West African Food Composition Table is a revised version of the Food composition table `Composition of Selected foods from West Africa`, which was published in September 2010. It extends and updates the number of foods and values of components through data derived from the Mali Food Composition Table 2004, Nigeria, as well as analytical data from scientific articles. [text taken from the book]